2017
DOI: 10.1002/hpm.2479
|View full text |Cite
|
Sign up to set email alerts
|

Prospective systemic risk analysis of the dispensing process in German community pharmacies

Abstract: This analysis not only detected various potential safety issues concerning the dispensing in Germany but also strongly indicated that application of failure mode and effects analysis could be highly effective in prospective risk reduction in community pharmacies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 27 publications
8
18
0
1
Order By: Relevance
“…We found that FMEA is a valuable prospective analytical method that can be applied to most of the processes in healthcare. According to our study, FMEA can be successfully applied to evaluate the safety of existing procedures, 13 24 26 27 16-22 30–33 35 36 39–42 44–46 process changes 43 and assess the implementation of new policies. 29 Furthermore, we encountered studies which employed FMEA to evaluate the impact of different situations such as drug shortages 25 and to select the best choice over two alternatives.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We found that FMEA is a valuable prospective analytical method that can be applied to most of the processes in healthcare. According to our study, FMEA can be successfully applied to evaluate the safety of existing procedures, 13 24 26 27 16-22 30–33 35 36 39–42 44–46 process changes 43 and assess the implementation of new policies. 29 Furthermore, we encountered studies which employed FMEA to evaluate the impact of different situations such as drug shortages 25 and to select the best choice over two alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies had successfully implemented corrective measures after having FMEA discussions. 13 15–33 35–37 39–42 44–46 Although every single healthcare process has its own inherent risks, it is well known that areas such as chemotherapy, neonatology and paediatrics are areas that are more vulnerable to hazards. We learnt from the present systematic review that FMEA was effectively and widely used in such areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations